Fracture-driven weakening amplifies projected ice loss from West Antarctica - Javier Blasco; Violaine Coulon; Maaike Izeboud; Thomas Gregov; Yanjun Li; Frank Pattyn (Proceedings of the National Academy of Sciences, 2026)
Ice shelves buttress the flow of the Antarctic ice sheet, but this stabilizing effect weakens as fractures form, reducing ice viscosity and accelerating ice discharge toward the ocean. Here, we incorporate physically consistent damage mechanics into an ice-sheet model and apply it across the Amundsen Sea Embayment, the largest current contributor to Antarctic mass loss. Simulations reproduce key satellite-derived damage patterns under present-day conditions. Projections to 2300 show that allowing damage to evolve strongly amplifies future ice loss, increasing sea-level contributions by up to a factor of ∼ 4.5. Even when damage is held fixed at its present-day extent, projected contributions increase by 50 to 130 % , indicating that existing fractures already commit the system to enhanced ice loss. Basal crevasses dominate this response, accounting for ∼ 90% of damage-induced amplification. Healing mechanisms substantially moderate damage, as neglecting gravitational crevasse closure and compressive healing overestimates ice loss by almost 50%. Together, these results suggest that fracture-driven weakening substantially alters Antarctic ice-sheet dynamics and should be represented in projections of future sea-level rise.